2014
DOI: 10.1371/journal.pone.0086681
|View full text |Cite|
|
Sign up to set email alerts
|

The Non-Classical MAP Kinase ERK3 Controls T Cell Activation

Abstract: The classical mitogen-activated protein kinases (MAPKs) ERK1 and ERK2 are activated upon stimulation of cells with a broad range of extracellular signals (including antigens) allowing cellular responses to occur. ERK3 is an atypical member of the MAPK family with highest homology to ERK1/2. Therefore, we evaluated the role of ERK3 in mature T cell response. Mouse resting T cells do not transcribe ERK3 but its expression is induced in both CD4+ and CD8+ T cells following T cell receptor (TCR)-induced T cell act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…17 We have previously shown that ERK3 expression is induced via ERK1/2 in mature T cells following TCR stimulation. 18 We also reported that Erk3 is transcribed during thymic T-cell differentiation with the highest level of expression in DN and DP thymocytes. 19 Inactivation of the Erk3 gene leads to a reduction in thymic cell number that is caused by a twofold reduction in DP thymocyte number because of their reduced survival during the rearrangement of the TCR-a chain.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…17 We have previously shown that ERK3 expression is induced via ERK1/2 in mature T cells following TCR stimulation. 18 We also reported that Erk3 is transcribed during thymic T-cell differentiation with the highest level of expression in DN and DP thymocytes. 19 Inactivation of the Erk3 gene leads to a reduction in thymic cell number that is caused by a twofold reduction in DP thymocyte number because of their reduced survival during the rearrangement of the TCR-a chain.…”
Section: Introductionmentioning
confidence: 76%
“…We have previously shown that ERK3 expression is induced by the classical MAPK ERK1/2 in mature T cells . The fact that ERK3 is already expressed in DP thymocytes, even within the DP thymocytes that have not undergone positive selection, suggests that its expression is induced by pre‐TCR signalling, which activates ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While ERK4 knockout mice appeared normal, ERK3 knockout mice were not viable, displaying retarded intrauterine growth and pulmonary hypoplasia leading to acute perinatal respiratory failure (17). Furthermore, T-cell development, selection, and activation was impaired only in ERK3, but not in ERK4, knockout mice (19)(20)(21). The lack of phenocopy between both knockouts suggested distinct and nonredundant functions of the ERK3/ MK5 and ERK4/MK5 signaling complexes.…”
mentioning
confidence: 99%